Correlation between Blood Pressure and Severity of Atherosclerosis in The Left Main Coronary Artery with CT Coronary Angiography Examination - Esis Prasasti Inda Chaula; Nurdopo Baskoro (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Background: Cardiovascular disease, especially hypertension, is the main cause of death in both developed and developing countries. Hypertensioncan lead to atherosclerosis, which is the most common cause of ischemic and coronary heart disease. Some countries have used Computed Tomography Coronary Angiography (CTCA), which is a noninvasive test, to observe the anatomy of coronary artery. Nevertheless, invasive angiography isstill the gold standardfor coronary artery visualization. Atherosclerotic plaques cancause left main coronary artery stenosis. Purpose: The purpose of this research is to analyze the correlation between blood pressure and severity of the atherosclerosis in the left main coronary artery. With CTCA examination, the presence of plaque, severity of stenosis and type of plaques were assessed. Methods: The study design was analytic observational with cross sectional design. Data was drawn from medical records. The sample included a total of 29 patients which were suspected of having coronary heart disease and examined with CTCA who meet inclusion and exclusion criteria in Dr. Kariadi Hospital, Semarang, Indonesia. Result: The correlation between systolic blood pressure and left main coronary artery stenosis was obtained by Spearman’s rho r = 0.0429, p-value of with of 0.020 (2-tailed). The correlation between diastolic blood pressure and left main coronary artery stenosis was obtained by Spearman’s rho r = 0.354 with p-value of 0.060(2 -tailed). Some types of plaques were found in left main coronary artery, and systolic blood pressure are significantly different analysed usingAnova (analysis of variance) which probability was significant with p value 0.041. Conclusion: There was a significant correlation between systolic blood pressure and left main coronary artery stenosis. Therewas no correlation between diastolic blood pressure and left main coronary artery stenosis. Furthermore, there was a significant difference between systolic blood pressure and the type of plaques in the left main coronary artery.